G277(P) Worldwide short course education programmes in epilepsy for paediatricians – are they effective?. (May 2019) - Gifford, A; Wilmshurst, J; O'Callaghan, F; Griffiths, M; Dunkley, C; Rodie, P; Cross, H; Kirkpatrick, M
Abstract : The UN Sustainable Development Goals include reduction in premature mortality from non-communicable disease and training of the healthcare workforce. Peer-supported workshop-based training is a proven effective training tool. The PET (Paediatric Epilepsy Training – BPNA/ILAE) programmes have recently expanded across five continents aiming to educate clinical professionals in the recognition, investigation and management of childhood epilepsy. A one-day standardised curriculum promotes evidence-based, safe practice which is delivered by a trained faculty to a target audience, primarily paediatricians and specialist nurses. A pragmatic framework was used to measure the effectiveness of these courses. Data were recorded on attendance, reaction to the course delivery, knowledge gain and changes in practice six months after the course. 6781 clinicians attended a PET Level 1 course over the last 15 years. 29% then 59% of participants scored the course as 'excellent' before and after its 2015 revision. Level of seniority and experience did not affect participants' positive reaction (R2=0.05). Knowledge scores pre and post course increased from 76% to 90%, with incorrect answers identifying areas of clarification subsequently implemented in course material revision. Self-reported changes in practice six months following the course by the 323 participants who responded from India, Kenya, Myanmar, New Zealand, South Africa, Sudan and the UK included 66% reporting significant or moderate changes to their personal practice in epilepsy care. In 2017, specific reported improvements included improved history-taking (82%), ability to distinguish epileptic and non-epileptic events (85%), no longer prescribing anti-epileptic drugs for febrile seizures (42%) and improved prolonged seizure management (54%). A clear trend to greater reported improvements from low and middle-income country settings was seen. In Sudan, 26% had developed a dedicated epilepsy clinic since the course. This international survey included medication and diagnostic resource availability. Intravenous lorazepam was available to only 52% across all sites, emphasising the need for region-specific guidelines of prolonged seizures. Only 51% of respondents from India had access to video EEG and 15% to an epilepsy specialist nurse. These pilot data provide evidence for the effectiveness of short-course epilepsy education for clinicians to improve the quality of care for children with epilepsy globally.